Criminal Law Consequences of Freedom of Expression on Social Media According to Law Number 1 of 2024 Concerning the Second Amendment to Law Number 11 of 2008 Concerning Electronic Information and Transactions - Elfaiz, Fariz; Zahri, Saiuddin; Wardhana, Arief Wisnu; Sastro, Harmonis (Polteknik Ilmu Pemasyarakatan, 2025)
In the digital era, the freedom of expression granted to individuals through social media has the potential to be misused, such as by spreading information that is unlawful or harmful to others. In this context, it is important to analyze the legal regulations governing freedom of expression in digital spaces, with a focus on the 1945 Constitution of the Republic of Indonesia, Law Number 11 of 2008 on Electronic Information and Transactions (ITE Law), the latest amendment in Law Number 1 of 2024, and Article 23 paragraph (2) of Law Number 39 of 1999 on Human Rights. This study aims to understand how the boundaries of freedom of expression can be applied in digital spaces in accordance with existing legislation and to identify appropriate solutions for regulating expression on social media and cyberspace. This research uses a normative approach through literature and document studies, analyzed using descriptive qualitative methods. The findings indicate that although freedom of expression is guaranteed, restrictions must be implemented to maintain public order and to respect the rights of others, particularly in the context of social media and cybercrime. Implications for society, understanding freedom of speech on social media which must be carried out responsibly is crucial and law enforcement officers must be able to interpret the articles in the ITE Law fairly and proportionally.